Evaluación de la influencia de los recursos computacionales en la QoE del servicio. - Baena-González, José Carlos; Hervás Gutiérrez, María; Baena-Martínez, Eduardo; Villegas, Javier; Barco-Moreno, Raquel; Fortes-Rodríguez, Sergio (My University, 2023)
The new generation of mobile networks goes beyond radio communications by providing a resilient and flexible architecture. In this context, the virtualization of Radio Access Networks (vRAN) completes the Network Func4on Virtualization (NFV) milestone, enabling a distributed and scalable network architecture. However, this approach increases the complexity of management tasks as computing resources start to play an essential role in the network provisioning process. In this sense, this work aims to assess the impact of computational resources on the delivery of video streaming services. The results obtained prove that inadequate resource assignment to vRAN instances leads to degradation of the Quality of Experience (QoE), even if the allocation of radio resources is adequate for the service.
Keywords: Sistemas de comunicaciones móviles; Virtualización; vRAN; QoE; 5G